Al-Dhawadi, Mahmoud. “New Insights on the Nature of Culture in the Islamic Epistemological View,” Year 11, Issues 42-43 (Fall 1426 AH/ 2005 CE), Pp. 127-160. - الذوادي, محمود (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2006)
Mahmoud al-Dhawadi’s article aims to provide primary in-depth research regarding the essence of things and their cultural foundations from an Islamic epistemological perspective; doing so through a comparative study between the concept of culture in the Arab and Islamic perspective and their Western counterpart. The article addresses: the definition of culture in sociology; the nature of culture in the Islamic epistemological view; the Qur’anic epistemological view of culture; indicators of metaphysical features of cultural symbols; manifestations of metaphysical aspects in cultural symbols such as language, values of freedom, justice, and equality; and the Arab Ummah and its cultural ʿaṣabiyyah (solidarity/identity).